Measuring Employee Performance in the Age of Remote Work: Key Metrics and Challenges - Novita, Wellia; Edriani, Devi (Takaza Innovatix Labs Ltd., 2024)
This study examines the impact of the remote work environment on employee performance and key metrics for performance measurement, focusing on the mediating role of challenges in remote work. Using a quantitative approach, data were collected from 60 employees at PT. GIEB Indonesia through structured electronic surveys. The results, analysed through Structural Equation Modeling (SEM) using Smart PLS, indicate that while the remote work environment does not directly influence employee performance, it significantly affects performance indirectly through the challenges employees face. These challenges, such as communication difficulties, technical issues, and work-life balance, were critical in determining employee performance and achieving key performance metrics. The findings suggest that organisations must address these challenges by providing appropriate support and resources to improve remote work effectiveness, enhance employee productivity, and ensure accurate performance evaluation. This study contributes valuable insights into optimising remote work strategies and managing employee performance in a digitally driven work landscape.